Mapping Carbon Pricing Initiatives : Developments and Prospects 2013 - Kossoy, Alexandre (World Bank, Washington, DC, 2013)
The Mapping Carbon Pricing Initiatives Report maps existing and emerging carbon pricing initiatives around the world. It does not provide a quantitative, transaction-based analysis of the international carbon market since current market conditions invalidate any attempt to undertake such an analysis. The development of national and subnational carbon pricing initiatives in an increasing number of countries calls for a different focus. The uncertainty surrounding the existing carbon markets in the last years has prevented valuable resources to be channeled to low-carbon investments, particularly from the private sector. Following the economic downturn and slow economic recovery in major economies, industrial output plummeted and the demand for carbon assets used for compliance fell. With limited support, prices reached historical lows. At the same time, several national and sub-national carbon pricing initiatives are emerging. It is not surprising that several of these new carbon pricing initiatives also include design features to prevent similar developments in the future, including mechanisms to stabilize the carbon price.